We have the graphs of the functions
f(x) ------ the left graph in the picture
g(x) ----- the right graph in the picture
We need to find
![(f+g)(3)](https://img.qammunity.org/2023/formulas/mathematics/college/tfruldmsf9k6i2e0yb5l1b7ai6x7bxlbxd.png)
This means we need to find
![f(3)+g(3)](https://img.qammunity.org/2023/formulas/mathematics/college/a1duoidpo3ceijiu1tbo9c3u9g49wldpi7.png)
To find f(3) look at the left graph
Look for the value of y at x = 3
At x = 3 the value of y is 0, then
![f(3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/y9m4xf6zlphr49voxbspp6obad9z2win0y.png)
To find g(3), look at the right graph
Look for the value of y at x = 3
At x = 3 the value of y is 0, then
![g(3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/83f44e2r2bduo0dvg3cf6o24wswmrpzddt.png)
Add them
![\begin{gathered} f(3)+g(3)=0+0 \\ (f+g)(3)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s3i0rtkw42viztvtcha1uitjyk6kjk40g0.png)
a)
(f + g)(3) = 0
We need to find
![(f-g)(2)](https://img.qammunity.org/2023/formulas/mathematics/college/bx4d2dybaeufx4mtq6d3jx5iwd7ii705b0.png)
That means we need to find
![f(2)-g(2)](https://img.qammunity.org/2023/formulas/mathematics/college/la4uqa4tstlnmdyfnjbxfbp0v11yqp6k8q.png)
To find f(2) look at the left graph
Look for the value of y at x = 2
At x = 2 the value of y is 1, then
![f(2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/mohytzpwwr38hj3759mnwpavbyb3mkvv5u.png)
To find g(2) look at the right graph
Look for the value of y at x = 2
At x = 2 the value of y is 4, then
![g(2)=4](https://img.qammunity.org/2023/formulas/mathematics/college/xupk8ngi3b7wkwycj9xj7w19tbmhcmvryy.png)
Subtract them
![\begin{gathered} f(2)-g(2)=1-4 \\ \\ (f-g)(2)=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ug7gbxyml1iygnehlxl1u4xb4zx3iwyr6z.png)
b)
(f - g)(2) = -3